Aplicações de ágebra linear aos códigos corretos de erros e ao ensino médio - Nicoletti, Everton Rodrigo [UNESP] (2015)
The present work addresses basic concepts of Linear Algebra and its applications in the development of the Theory of Error Correcting Codes. The use of this mathematical tool simpli es the generation and decoding of linear codes. This dissertation also highlights the importance of working with this subject in high school